2004
DOI: 10.1126/science.1098496
|View full text |Cite
|
Sign up to set email alerts
|

Mars' South Polar Ar Enhancement: A Tracer for South Polar Seasonal Meridional Mixing

Abstract: The gamma ray spectrometer on the Mars Odyssey spacecraft measured an enhancement of atmospheric argon over southern high latitudes during autumn followed by dissipation during winter and spring. Argon does not freeze at temperatures normal for southern winter (approximately 145 kelvin) and is left in the atmosphere, enriched relative to carbon dioxide (CO2), as the southern seasonal cap of CO2 frost accumulates. Calculations of seasonal transport of argon into and out of southern high latitudes point to merid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 12 publications
11
78
1
Order By: Relevance
“…The OMEGA data suggest an enhancement over Hellas at Ls = 130−150 deg (end of southern winter), by a factor of about 2 with regard to Ls = 330−350 deg (end of northern summer). This behavior is to be compared with the evolution of argon, another non-condensible species which also shows strong variations with Ls at southern latitudes (Sprague et al 2004). This result appears also consistent with the GCM predictions which indicate an enrichment by a factor of about 2 of non-condensible species over Hellas during southern winter (Forget et al 2006).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The OMEGA data suggest an enhancement over Hellas at Ls = 130−150 deg (end of southern winter), by a factor of about 2 with regard to Ls = 330−350 deg (end of northern summer). This behavior is to be compared with the evolution of argon, another non-condensible species which also shows strong variations with Ls at southern latitudes (Sprague et al 2004). This result appears also consistent with the GCM predictions which indicate an enrichment by a factor of about 2 of non-condensible species over Hellas during southern winter (Forget et al 2006).…”
Section: Introductionsupporting
confidence: 73%
“…Such an effect was first noticed by Krasnopolsky (2002) who reported latitudinal variations of the CO mixing ratio from 800 ppm north of 23N up to 1200 ppm at 50S latitude during early northern summer (Ls = 112 deg). The seasonal variation of argon, another non-condensible species, has been also detected by the Gamma Ray Spectrometer (GRS) aboard Mars Odyssey (Sprague et al 2004). An enhancement by a factor as high as 6 was reported at high southern latitudes during southern winter (Sprague et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most trace gases however do not condense with CO 2 , and become enriched in terms of their volume mixing ratio (vmr). This enrichment has been observed in polar measurements of argon by GRS on Mars Odyssey (Sprague et al 2004). From measurements of CO at lower latitudes by CRISM on MRO (Smith et al 2009b), it was observed that towards the end of the southern summer, the polar hood that is by then fully enriched in CO, will start to leak this enriched air towards lower latitudes.…”
Section: Non-condensable Gasesmentioning
confidence: 84%
“…A recent study of Omega/Mars Express data showed that variations as a function of the seasonal cycle of the CO mixing ratio could reach a factor of 2 above the Hellas Basin . It is also likely that the atmosphere above the southern condensing polar cap is enriched in CO, similarly to other non-condensable gas such as argon for which this enrichment (by a factor of at least 6) has been detected by Mars Odyssey (Sprague et al 2004).…”
Section: Introductionmentioning
confidence: 99%